Topeng Bondres Sebagai Media Penyuluhan Agama Hindu Oleh Penyuluh Agama Hindu Kementerian Agama Kabupaten Buleleng - I Nyoman Ariyoga; I Gede Sutana; Gede Agus Jaya Negara; Duwi Oktaviana (Jayapangus Press, 2023)
Hindu religious instructors or prospective Hindu religious instructors must have strategies and innovations in providing counseling. The strategy is certainly expected to be able to have a significant impact so that the extension material delivered can be easily accepted, understood and understood by the community. The Hindu religious instructor at the Buleleng Regency Ministry of Religion also uses the Bondres mask art as one of the media in Hindu religious education. Bondres mask art performances that are full of jokes and invite laughter from the audience are very effective as a method of Hindu religious education. In this study, the researchers wanted to explore further related to the counseling strategy by Hindu religious instructors using Bondres Mask media, the supporting and inhibiting factors for Hindu religious counseling using Bondres Mask media, and the implications of using Bondres masks as a medium for Hindu religious education. This type of research is qualitative research with data collection techniques in this study consisting of observation, literature study, and interviews. Data analysis consists of: data reduction, data presentation, conclusion drawing and verification. The discussion is: 1 the counseling strategy carried out by the Hindu religious counselor is: a) determining the message of dharma, b) performing aesthetic communication c) good blocking on stage d) sound instrument or accompaniment music. 2 supporting factors, namely: a) support morale, b) enthusiasm of the community. Meanwhile, the inhibiting factors are: a) rhetorical ability, b) material is not optimal, c) infrastructure d) staging time. 3 the implications of the use of bondres masks are: a) Improving the human resources of bondres dancers, b) improving facilities and infrastructure, c) increasing public understanding, d) establishing harmonious relationships, e) people being able to distinguish between religious dharma and state dharma.